Antimicrobial test of roselle (hibiscus sabdariffa L.) ethanol extract againts porphyromonas gingivalis and streptococcus sanguis using agar method (in vitro study) - Lenni Indriani; Mohammad Dharmautama (Journal of Dentomaxillofacial Science, 2016)
The use of natural materials in the world of health tends to increase every single year, including  in dentistry. Due to the increased of resistance to antibiotics, the development and new innovations to obtain a new antimicrobial agent. Some potential sources of plants have been studied. One of the natural plants is used as drinks, food, medicine and antimicrobial agent is Hibiscus sabdariffa Linn commonly known as Roselle. Several major Gram-negative bacteria are related to periodontal disease such as Porphyromonas gingivalis (P.gingivalis), The dominant species of Gram-positive including Streptococcus sanguis(S.sanguis). The purpose of this in vitro study is to evaluate the Roselle ethanol extract against P.gingivalis bacteria (Gram negative bacteria) and S. sanguis (Gram positive bacteria) with a concentration of 2.5%, 5%, 7.5% and 10%. The in vitro study of antibacterial effectiveness of Roselle (Hibiscus sabdariffa L.) ethanol extract on P.gingivalis and S. sanguis. Natrium Agar (NA) solution was poured into a glass plate which had previously been sterilized and then left in place until the medium solidified. P.gingivalis and S.sanguis bacterial cultures were inoculated with inscribed which had solidified. Then put paper disk which had previously been saturated with Roselle extract samples with a concentration of 2.5%, 5%, 7.5% and 10%, and the negative control at the surface of the medium (Ampicillin) and incubated for 1 day. Clear zone is formed then observed and measured. There are 24 samples, consisting of 12 samples  P.gingivalis and S.sanguis 12 samples, given intervention roselle flower extract with four types of concentrations to determine the minimum inhibitory consentration (MIC). The observations show that the extensive zone of inhibition concentration of 2.5% a broad zone of inhibition is the smallest among other concentration, both of S.sanguins and P.gingivalis. Meanwhile, the average increases the broad zones of inhibition of P.gingivalis followed by increasing concentrations of roselle flower extract, making it the largest broad zones of inhibition are shown at a concentration of 10%, However, the bacteria S.sanguins, shows that vast zone of greatest inhibition was found at a concentration of 7.5%. The results of this research showed that the ethanol extract of roselle effectively inhibits P. gingivalis as Gram-positive bacteria atconcentrations of 10% and S. sanguins at a concentration of 7.5%. Iit can be concluded that the ethanol extract of roselle flowers effective at inhibiting Gram positive and Gram negative bacteria.